PENGARUH PENAMBAHAN BONGGOL PISANG TERHADAP DAYA TERIMA DAN KANDUNGAN GIZI NUGGET AYAM - Astri muliani; Ernawati Nasution; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Low nutrient status of one of them is caused by the tendency of people who like to eat fast food that generally contain less fiber. Banana hump is a functional food that has great benefits, but the level of consciousness to consume and use it is still low, though the banana tree is a plant that thrives in Indonesia. This food can be processed into additional ingredients in making chicken nuggets, one of the fast food that people love. Type of research is experiment. The power test receipt uses a complete randomized design study with organoleptic tests to see the panelist's preference for food. The subjects of acceptance test are 30 people who are college students of the Faculty of Public Health University of North Sumatra. The object of this research is chicken nuggets with the addition of 10%, 20% and 30% banana hump from the weight of the main ingredient. The nutritional content seen includes protein and fiber. Chicken nugget with the addition of banana hump has the highest 12.81% protein content found in chicken nugget with the addition of 10% banana hump and the highest coarse fiber found in chicken nugget with the addition of 30% banana hump that is equal to 6,60%. The results of the organoleptic test, the panelists prefer chicken nugget with the addition of 10% banana hump in color, smell and taste indicator which each has a score of 88.8%, 93.3%, 80% with criteria like, while for textures indicator panelists prefer chicken nuggets with the addition of 30% banana humps that have a score of 83.3% with criteria like. Chicken nugget with the addition of banana humps produced can be used as alternative food. Banana humps can be recommended for ingredients in chicken nuggets that have higher fiber content. Keywords: Chicken Nugget, Banana hump, Acceptance, Nutrition Content.